Let-7g Improves Multiple Endothelial Functions Through Targeting Transforming Growth Factor-Beta and SIRT-1 Signaling - Liao, Yi-Chu; Wang, Yung-Song; Guo, Yuh-Cherng; Lin, Wen-Lien; Chang, Ming-Hung; Juo, Suh-Hang Hank (Journal of the American College of Cardiology, 2014)
The present study aimed to explore the role of microribonucleic acid (miRNA) Let-7g in regulating endothelial functions. Derangement of miRNAs is implicated in the pathogenesis of cardiovascular diseases. Because the transforming growth factor (TGF)-β pathway plays a regulatory role in endothelial functions, miRNAs targeted at TGF-β signal cascade might affect vascular health. Bioinformatics software predicted that Let-7g can influence the TGF-β pathway by targeting 3 genes. The Let-7g's effects on multiple endothelial functions were first tested in endothelial cells (ECs) and then in apolipoprotein E knockout mice. Blood samples from lacunar stroke patients were also examined to further support Let-7g's effects on human subjects. Let-7g was experimentally confirmed to knock down the THBS1, TGFBR1, and SMAD2 genes in the TGF-β pathway. PAI-I, one of the downstream effectors of the TGF-β pathway, was also down-regulated by Let-7g. Let-7g decreased EC inflammation and monocyte adhesion and increased angiogenesis via the TGF-β pathway. Furthermore, Let-7g reduced EC senescence through increasing SIRT-1 protein. Venous injection of Let-7g inhibitor into apolipoprotein E knockout mice caused overgrowth of vascular intima-media, overexpression of PAI-1, increased macrophage infiltration, and up-regulation of TGF-β downstream genes in the carotid arteries. Let-7g's beneficial effects on EC were reduced, whereas the TGF-β pathway was suppressed by ribonucleic acid interference. Restoration of the TGF-β pathway also attenuated the effects of Let-7g overexpression. Low serum levels of Let-7g were associated with increased circulating PAI-1 levels. Decreased Let-7g levels impair endothelial function and increase the risks of cardiovascular diseases through targeting TGF-β and SIRT-1 signaling.